2015
DOI: 10.14257/astl.2015.114.08
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Value on Customer Loyalty in a Low-Priced Cosmetic Brand of South Korea: The Moderating Effect of Gender

Abstract: Abstract. The purpose of this paper investigates the effect of perceived value on customer loyalty through brand image and customer satisfaction in a lowpriced cosmetic brand, as well as to examine the moderating role of gender. The results showed that perceived value positively affects brand image and customer satisfaction. Brand image positively influences customer loyalty but does not influence customer satisfaction. Customer satisfaction has a positive effect on customer loyalty. The moderating effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
5
1
1
Order By: Relevance
“…A company that has a good image in the customers' mind will attract the customer to use the same service provided by the same company, do re-purchase, and recommending the service to other people. This result support the result of research by Wu (2011) and Chung et al, (2015) who find that companies' image has a positive effect on customers' loyalty.…”
Section: The Effect Of Hospital Image On Patients Loyaltysupporting
confidence: 90%
“…A company that has a good image in the customers' mind will attract the customer to use the same service provided by the same company, do re-purchase, and recommending the service to other people. This result support the result of research by Wu (2011) and Chung et al, (2015) who find that companies' image has a positive effect on customers' loyalty.…”
Section: The Effect Of Hospital Image On Patients Loyaltysupporting
confidence: 90%
“…This outcome is similar to the earlier studies (Pham & Nguyen, 2019;Lien et al, 2015), which report that favourable brand image directly affects the perceived value. However, this result differs from the study of prior authors (Chung, Yu, Kim & Shin, 2015;Yan, 2019), who found that enhanced perceived value enhances the image of brands. Thus, the study's outcome demonstrates that a favourable and strong image contributes to strengthening the perceived performance, monetary, emotional and social value of the brands in the OTC herbal market.…”
Section: Discussioncontrasting
confidence: 99%
“…As compared to males, females are more functional and appearanceconscious out of other BI benefits like social and experiential (Sondoh et al, 2007), especially when they shop cosmetic products (Thakur & Singh, 2012). This is not supported by Chung et al (2015).…”
Section: H 4a and H 4bmentioning
confidence: 67%
“…The research focused on analysing the individual effect of CI and BI on CL and WOM and identifying the influence of CL on WOM and CI on BI. The electronics industry is considered as price sensitive across the country (Chung et al, 2015). However, the durable consumer industry remains least explored while studying the literature for CI, BI, CL and WOM.…”
Section: Discussionmentioning
confidence: 99%